Decision Support for Mitigation of Livestock Disease: Rinderpest as a Case Study - Mourant, Judith R.; Fenimore, Paul W.; Manore, Carrie A.; McMahon, Benjamin H. (Frontiers in Veterinary Science, 2018)
A versatile, interactive model to predict geographically resolved epidemic progression after pathogen introduction into a population is presented. Deterministic simulations incorporating a compartmental disease model run rapidly facilitating the analysis of mitigations such as vaccination and transmission reduction on epidemic spread and progression. We demonstrate the simulation model using rinderpest infection of cattle, a devastating livestock disease. Rinderpest has been extinguished in the wild, but it is still a threat due to stored virus in some laboratories. Comparison of simulations to historical outbreaks provides some validation of the model. Simulations of potential outbreaks demonstrate potential consequences of rinderpest virus release for a variety of possible disease parameters and mitigations. Our results indicate that a rinderpest outbreak is highly likely to result in severe social and economic consequences.